Ethnomedical practices and the dynamics of local Knowledge: participatory survey among populations in the Fez Meknes region - Doubi, Meryem; el Khomsi, Mostafa; Allali, Aimad; Torres, Chaimae; el Assri, Youssef; Amrani el Medrai, Inssaf; Khemmou, Nidal; Lahkimi, Amal; Hmouni, Driss (Ethnobotany Research and Applications, 2026)
Background: Medicinal and aromatic plants are essential for therapeutic, food, and cosmetic uses. Objectives: to promote local knowledge and document floral diversity and ethnobotanical practices. Methods: An ethnobotanical survey (March 2024–March 2025) was conducted among 406 participants in Fez-Meknes Region, Morocco. The data, obtained from semi-open interviews on therapeutic, dietary, and cosmetic practices, were used to calculate Family Use Value (FUV), Use Value (UV), Plant Part Value (PPV), and Informant Agreement Ratio (IAR). Multiple correspondence analysis (MCA) explored the links between plant use and sociodemographic characteristics. Results: 123 species belonging to 55 botanical families were enumerated, The Lamiaceae family (FUV=0.154) was found to be the most represented, while Ajuga iva (L.) Schreb. (UV=0.57) was the most recommended species. Maceration is the most common method of preparation (63.87%). Leaves are the most commonly used part (PPV=0.78). Painful and inflammatory conditions were the most frequently cited category (IAR=0.96). Conclusions: Present study highlights the richness of flora and traditional knowledge, and the importance of phytochemical and pharmacological research in scientifically validating therapeutic, dietary, and cosmetic uses. Keywords: Ethnopharmacology, Traditional medicine, Medicinal plants, Use value/IAR.